The prima donna's album : 42 celebrated Arias from Famous operas - ADLER, Kurt (ed) (G. Schirmer. Inc.)
Durch Zartlichkeit und schmeicheln, Ach ich liebte, Morro ma prima in grazia, Volta la terrea fronte alle stelle, Ah my darling we could grow together, Donde lieta, Quando men vo solleta,Voi lo sapete, To this we've come